A short isoform of the UNC-6/Netrin receptor UNC-5 is required for growth cone polarity and robust growth cone protrusion in Caenorhabditis elegans - Mahadik, Snehal S.; Lundquist, Erik A. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: UNC-6/Netrin is a conserved bi-functional guidance cue which regulates dorsal-ventral axon guidance in C. elegans. In the Polarity/Protrusion model of UNC-6/Netrin mediated dorsal growth away from UNC-6/Netrin, The UNC-5 receptor first polarizes the VD growth cone such that filopodial protrusions are biased dorsally. Based on this polarity, the UNC-40/DCC receptor stimulates growth cone lamellipodial and filopodial protrusion dorsally. The UNC-5 receptor maintains dorsal polarity of protrusion, and inhibits growth cone protrusion ventrally, resulting in net dorsal growth cone advance. Methods: Growth cone imaging in mutants, combined with Cas9 genome editing and genetic analysis, were used to analyze the role of a novel short isoform on unc-5 in growth cone polarity and protrusion. Results: Work presented here demonstrates a novel role of a previously undescribed, conserved short isoform of UNC-5 (UNC-5B). UNC-5B lacks the cytoplasmic domains of UNC-5 long, including the DEATH domain, the UPA/DB domain, and most of the ZU5 domain. Mutations that specifically affect only the unc-5 long isoforms were hypomorphic, suggesting a role of unc-5B short. A mutation specifically affecting unc-5B caused loss of dorsal polarity of protrusion and reduced growth cone filopodial protrusion, the opposite of unc-5 long mutations. Transgenic expression of unc-5B partially rescued unc-5 axon guidance defects, and resulted in large growth cones. Tyrosine 482 (Y482) in the cytoplasmic juxtamembrane region has been shown to be important for UNC-5 function, and is present in both UNC-5 long and UNC-5B short. Results reported here show that Y482 is required for the function of UNC-5 long and for some functions of UNC-5B short. Finally, genetic interactions with unc-40 and unc-6 suggest that UNC-5B short acts in parallel to UNC-6/Netrin to ensure robust growth cone lamellipodial protrusion. Discussion: These results demonstrate a previously-undescribed role for the UNC-5B short isoform, which is required for dorsal polarity of growth cone filopodial protrusion and to stimulate growth cone protrusion, in contrast to the previously-described role of UNC-5 long in inhibiting growth cone protrusion.